'They don't read metres, they only bring bills': Issues surrounding the installation of prepaid water metres in Karoi town, Zimbabwe. Issue 3 (1st September 2020) - Reniko, Gondo; Kolawole, Oluwatoyin D.
ABSTRACT: City and town administrators in Zimbabwe continue to push for the installation of prepaid water meters (PWMs). This is despite the residents' objections to the proposal. The merits and demerits of PWMs continue to be debated, and more empirical information will help chart a new course especially in smaller cities in poor countries. The paper adopts a qualitative research design and case study approach in eliciting information from respondents. Water governance institutions and 35 residents in Karoi town were purposively sampled to understand how they viewed the impact of PWMs installation in the water supply chain. Data collection tools included questionnaires, documents, observations and focus group discussions (FGDs). Findings revealed that respondents perceived water is an indispensable commodity, a right and one that should be enjoyed by every citizen regardless of their social or economic status. The installation of PWMs also runs contrary to the Zimbabwean Constitution as it deprives low-income citizens of water if they could not afford to pay. Instead, a more appropriate delivery mechanism is the traditional post-paid system, which allows consumers to access water based on affordability.